PERFORMANCE EVALUATION OF A MANUALLY OPERATED DRIP IRRIGATION SYSTEM MADE OF BAMBOO MAINS, LATERALS AND SUB-LATERALS - Biswas, R.K. (Journal of Soil and Water Conservation, 2022)
A drip irrigation system developed by using the bamboo made mains, laterals and sub-laterals was tested for its performance in irrigating the banana crop of 0.2 ha. The pressure in the system was created about 3.5 m of water from an overhead tank where water was lifted by operating a hand tubewell. The unifor- mity coefficient in distribution of water at plant bottoms and losses of water through the system were found 93.02 and 9092%, respectively. The average rate of discharge through each sub-lateral was 24.02 cm3/min. The maximum area of 0.2 ha of banana crop may be covered through this drip system by unit manpower. The cost of drip network was Rs. 33,300/ha. The bamboo drip system studied here may be installed by semi-skilled labour and locally available available materi- als. This initial cost is about 26% lesser compared to commercial drip network of PVC for plant spacing of 2m x 2m